PROGRAM PENERAPAN LIGABEL (LANSIA JAGA BALANCE) TAHAP EXERCISE TRAINING PADA KADER POSYANDU LANSIA PUCANG SAWIT DI SURAKARTA - Asita Rohmah Mutnawasitoh; Dita Mirawati; Tri Susilowati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Elderly people go through a degenerative process that causes a decline in neuromusculoskeletal and vestibular function, resulting in balance disorders that increase the risk of falls. The Elderly Maintain Balance program is a Community Service Program (PKM) program implemented at the Senja Bahagia Pucang Sawit Integrated Health Post (Posyandu), Surakarta. The purpose of this activity is to improve the knowledge and balance of the elderly, as well as compliance with exercise. Evaluation of the activity was carried out by measuring the knowledge of the elderly using a questionnaire. Data analysis using the Wilcoxon test to determine the increase in balance, as well as compliance with exercise using a questionnaire, the results of which will then be described. The results of the community service activity showed that knowledge increased to 47.56%, there was an increase in balance with a p-value of 0.035, and there was compliance in carrying out exercises with a percentage of 87.93%. The community service activity was said to be successful in increasing knowledge, balance, and compliance in carrying out balancing exercises in the elderly in the Pucang Sawit area, Surakarta. This program can be used as an example for other areas in an effort to improve the welfare of the elderly through a holistic approach that actively involves the community.